Pravne posledice začetka postopka zaradi insolventnosti za predhodne odredbe - Potočnik, Maja (Podjetje in delo, 2013)
Pursuant to Article 260(1) of the Slovenian Enforcement and Securing of Civil Claims Act (ZIZ), the court may enforce attachments in aid of execution specified in detail under Sections 1 to 6. They include, inter alia, the act of prohibiting the Agency of Money Transfer to pay the debtor, or any other party upon the debtors order, any amount from their account for which such an attachment in aid of execution has been issued. An analysis of Article 260 demonstrates that ZIZ, with regard to any attachment in aid of execution relating to real estate, receivables and other property or material rights under Sections 1 to 3 of Article 260(1) of ZIZ, uses the term foreclosure, while for measures relating to the Agency of Money Transfer in line with Section 4 of Article 260(1) of ZIZ, the Act does not use the term foreclosure as it merely sets forth that any such attachment in aid of execution can be enforced to prohibit the Agency of Money Transfer to pay the debtor, or any other party upon the debtor's order, any amount from their account for which such an attachment in aid of execution has been issued. With attachments in aid of execution issued for any other purpose, except when prohibiting the Money Transfer Agency, it is undisputable that the creditor based on the issued attachment in aid of execution acquires the right to lien and the right to separate on the foreclosed assets. However, this leaves the question whether the act of prohibiting the Agency of Money Transfer to pay the debtor, or any other party upon the debtor's order, any amount from their account for which such an attachment in aid of execution has been issued in line with Section 4 of Article 260(1) of ZIZ, also represents a decision on foreclosure with all legal effects of a foreclosure from which the right to lien and to separate arises for the respective assets pursuant to an attachment in aid of execution.
Keywords: insolventnost; izvršba; izvršilni postopek; sodne odločbe